P1430BETA C-TERMINAL TELOPEPTIDE OF TYPE I COLLAGEN: CORRELATIONS WITH MINERAL METABOLISM PARAMETERS AND CARDIAC VALVULAR CALCIFICATIONS IN A COHORT OF HEAMODIALYSIS PATIENTS. (6th June 2020) - Regalia, Anna; Malvica, Silvia; Vettoretti, Simone; Pavone, Laura; Margiotta, Elisabetta; Castelnovo, Claudia; Scalamogna, Antonio; Messa, Piergiorgio
Abstract: Background and Aims: Beta-carboxyterminal telopeptide of type I collagen (beta-CTx) is considered a marker of bone resorption in patients affected by osteoporosis. Nevertheless, its role in mineral bone disorder (MBD) of CKD patients is not clear. The aim of this study was to explore in a group of haemodialysis patients (HDp): 1) The levels of beta-CTx; 2) The correlation between beta-CTx levels and other mineral metabolism (MM) parameters; 3) The association between beta-CTx and CKD-MBD specific therapy 4) The relation between beta-CTx and cardiac valvular calcifications (VC). Method: We studied a group of 21 HDp (F/M 9/12, age 68[54-78] years) randomly selected from the HDp actually followed-up in our Department. Dialysis vintage was 52[23-80] months. All HDp were on a three-weekly hemodialysis schedule, with a prescribed dialysate calcium of 1.5 mmol/l. Before the first dialysis session of the week, after the long interdialytic interval, the levels of beta-CTx, total and ionized calcium (tCa and iCa), Phosphorus (P), Magnesium (Mg), intact PTH (iPTH), total and bone isoform of alkaline phosphatase (tALP and bALP), 25-hydroxyvitamin D (25OHVD), 1, 25-dihydroxyvitamin D (1, 25OH2 VD), and other general biochemical parameters were measured (Figure 1 ). At the same time, data concerning MM therapies were recorded. In all the studied patients, the presence of VC was searched in the the most recent echocardiographic study. Results: The mean levels of beta-CTx in our cohort were 1828[1136-2214] ng/L. These value are similar to those reported in literature in HDp and significantly higher than those reported in general population. Beta-CTx levels showed a significant positive correlation with tALP (r 0.92, p <0.0001), bALP (r 0.89, p <0.0001) and iPTH (r 0.87, p<0.0001) and a negative correlation with tCa (r – 0.43, p=0.05) and iCa (r – 0.52, p=0.01). No significant correlation was found with the other MM and general biochemical parameters and with the general features of the studied cohort. 18 patients (85.7%) were taking P binders (72.2% Ca-based and 27.8% Ca-free). In 20 patients (95.2%) vitamin D therapy, either in the natural, active or both natural and active form (35%, 15% and 50%, respectively) was prescribed. 6 patients (28.6%) were in therapy with Cinacalcet. No difference was found in beta-CTx levels according to the presence and the type of each of the above mentioned therapies. VC were found in 38% of patients. Beta-CTx levels did not differ between VC positive and negative patients (2400±1406 ng/L and 1935 ±1339 ng/L, respectively, p=0.49) Conclusion: Taking into account the limitations of this preliminary small size observational study, our data showed that beta-CTx levels are high in HDp. Beta-CTx correlates with iPTH, tALP and bALP. The negative correlation with tCa and iCa probably might be influenced by the negative correlation between iPTH and serum Calcium. Beta-CTx levels are not associated with CKD-MBD specific therapy or with cardiac valvular calcifications. Further prospective and randomized studies, including a higher number of HDp and possibly bone histology are needed to elucidate the possible role of beta-CTx as a marker of bone disease in HDp.